2015
DOI: 10.3389/fpsyt.2015.00031
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Hypothalamic–Pituitary–Adrenal Axis Function Contributes to Altered Endocrine and Neurobehavioral Responses to Acute Stress

Abstract: Organisms react to environmental challenges by activating a coordinated set of brain–body responses known as the stress response. These physiological and behavioral countermeasures are, in large part, regulated by the neuroendocrine hypothalamic–pituitary–adrenal (HPA) axis. Normal functioning of the HPA axis ensures that an organism responds appropriately to altered environmental demands, representing an essential system to promote survival. Over the past several decades, increasing evidence supports the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 66 publications
4
77
0
3
Order By: Relevance
“…The 2,869 downregulated genes were mainly involved in metabolic processes, development process, DNA biosynthesis adjustment process, the cardiovascular system, cell adhesion, cell migration and positioning process. It has been shown that under acute stress conditions, mesenchymal stem cells and endothelial progenitor cells mobilize and provide a significant response, while HPA axia response and its key effect hormones-glucocorticoids exert an important regulatory effect (4547). Additionally, researchers have found that the gene expression of early BMSCs played a supporting role in nerve repair in the development of the nervous system (48), and the endogenous ligand of rat-derived BMSCs could be anti-apoptotic (49).…”
Section: Discussionmentioning
confidence: 99%
“…The 2,869 downregulated genes were mainly involved in metabolic processes, development process, DNA biosynthesis adjustment process, the cardiovascular system, cell adhesion, cell migration and positioning process. It has been shown that under acute stress conditions, mesenchymal stem cells and endothelial progenitor cells mobilize and provide a significant response, while HPA axia response and its key effect hormones-glucocorticoids exert an important regulatory effect (4547). Additionally, researchers have found that the gene expression of early BMSCs played a supporting role in nerve repair in the development of the nervous system (48), and the endogenous ligand of rat-derived BMSCs could be anti-apoptotic (49).…”
Section: Discussionmentioning
confidence: 99%
“…Techniques for riboprobe synthesis are described in greater detail elsewhere (Makino et al, 1994b). A thorough description of tissue preparation and the in situ hybridization protocol can also be found elsewhere (Kinlein et al, 2015). Based on the strength of autoradiographic signal on test slides exposed to X-ray film (Kodak BioMax MR film, Sigma, St. Louis, MO, USA), hybridized slides containing the PFC were exposed to film for 2 days to optimize the detection of possible treatment differences.…”
Section: Methodsmentioning
confidence: 99%
“…For example, treatment with IFNa induces major depression and this effect is, amongst others, related to alterations in the HPA axis (Castanon et al, 2014). The development of PTSD is also associated with HPA dysfunction, however, it is unclear whether this concerns hypo-or hyperfunction of the HPA axis (Kinlein et al, 2015). Finally, evidence grows that an altered communication across the gut-brain axis is associated with inflammatory-driven neuropsychiatric disorders (Castanon et al, 2014;Collins et al, 2012).…”
Section: Different Pathways Involved In the Neuroinflammatory Pathogementioning
confidence: 97%